2010
DOI: 10.1002/chin.201042161
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: New Quinoxaline 1,4‐Di‐N‐oxides: Anticancer and Hypoxia‐Selective Therapeutic Agents.

Abstract: New Quinoxaline 1,4-Di-N-oxides: Anticancer and Hypoxia-Selective Therapeutic Agents. -A series of novel quinoxaline 1,4-di-N-oxides is prepared and evaluated for antitumor and hypoxia-selective cytotoxic activities. Compound (VIb) is the most promising substance acting both as an antitumor and as a hypoxia-selective agent. Compounds (IIIb) and (Xd) are the most toxic against liver carcinoma (Hepg2). -(ISMAIL*, M. M. F.; AMIN, K. M.; NOAMAN, E.; SOLIMAN, D. H.; AMMAR, Y. A.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…179−181 Hypoxia-selectivity varies widely among these agents. 144,[173][174][175][176][177][178]182 Finally, some phenazine Noxides display properties similar to TPZ. 183 Redox-activated DNA cleaving activity has been described for phenazine Noxides including the natural product myxin (9).…”
Section: Structurally Diverse Heterocyclicmentioning
confidence: 99%
“…179−181 Hypoxia-selectivity varies widely among these agents. 144,[173][174][175][176][177][178]182 Finally, some phenazine Noxides display properties similar to TPZ. 183 Redox-activated DNA cleaving activity has been described for phenazine Noxides including the natural product myxin (9).…”
Section: Structurally Diverse Heterocyclicmentioning
confidence: 99%
“…The anticancer evaluation of the newly synthesized quinoxaline derivatives showed that among the tested compounds 8-bromo-4-chlorotetrazolo [1,5- (11) showed the best result, exhibiting the highest inhibitory effects towards the three tumor cell lines, which were higher than that of the reference doxorubicin and these compounds were non-cytotoxic on the normal cells (IC 50 values >100 µg/mL). In addition, compounds 4, 5a, 5b, 9 and 11-13 exhibited the highest degrees of inhibition against the strains of Gram positive and negative bacteria.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…Accordingly, we need to design new compounds having anticancer and antimicrobial activity at the same time. Quinoxaline derivatives display a broad spectrum of biological activities including antimicrobial [5][6][7], antiviral [8], antiinflammatory [9,10], anticancer [11][12][13][14], antimalarial [15], antitubercular, antileishmanial and kinase inhibitors [16][17][18][19]. Some quinoxaline derivatives have a cytotoxic effect on human cancer cell lines [20] and they constitute useful intermediates in organic synthesis and medicinal chemistry [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…2 Such compounds are also known to be active against transplant tumors. 4 Also, quinoxaline-based compounds have the ability to inhibit the metal corrosion and they are used in electroluminescent materials. 5,6 Physicochemical properties of inhibitors (e.g., electron density, geometric factors, molecular volume, etc.,) determine their effectiveness of corrosion, while the process of adsorption depends on the type of metal, the nature of inhibitor, and the electrochemical potential at the metal-solution surface.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Bearing in mind the biological, structural, and industrial importance of quinoxaline-and benzoxazine-based compounds, we used these previously synthesized compounds for DFT calculations. 13 The studied quinoxaline and benzoxazine derivatives namely 3,4-dihydro-3-[2-oxo-2-(4-methoxyphenyl) ethylidene]-2(1H)-quinoxalinone (1), 3,4-dihydro-3-(5-methyl-2-oxo-hex-5-enylidene)-2(1H)-quinoxalinone (2), 3,4-dihydro-3-[2-oxo-2-(3-nitrophenyl)ethylidene] -2(1H)-quinoxalinone (3) and 3,4-dihydro-3-[2-oxo-2-(3-N-acetylphenyl)ethylidene]-1,4-benzoxazin-2-one (4) are presented in Figure 1. In this study, the equilibrium conformation of selected compounds was predicted theoretically using B3LYP/6-311?G(d,p) level of theory.…”
Section: Introductionmentioning
confidence: 99%